Corrective Feedback Found In Speaking Class At The English Department Of Muhammadiyah University Of Surakarta - Anggoro, Ipung, Prof.Dr. Endang Fauziati, Aryati Prasetyarini, S.Pd, M.Pd (2013)
The major issue of this study is the implementation of corrective feedback in speaking class at UMS focusing on the types of corrective feedback used by the teacher in UMS, what is the frequency of each type of corrective feedback used by the teacher in teaching speaking in UMS, what is the dominant type of corrective feedback used by the teacher in teaching speaking in UMS, and what is the pedagogical implication of corrective feedback used by the teacher in UMS. The research is descriptive qualitative study. The subject of the study is teaching speaking I, II, III, IV in UMS. The object of the study is the first, second, third, and fourth year students' ability in speaking. To collect the data, the researcher uses observation and documentation in speaking class at UMS. The results of the study, show that there five types of corrective feedback used by the teachers in UMS, namely clarification request (59%), recast (19, 7%),metalinguistic feedback (14, 5%), explicit correction (3, 4%), and translation (3, 4%). The frequency of the use of clarification request found 69 data, recast 23 data, metalinguistic found 17 data, explicit correction found 4 data, and translation found 4 data. Therefore was the most dominant type of corrective feedback is clarification request where that was found 69 data. The implication of using corrective feedback on English speaking is that, the student will be brave in teaching learning activity especially on speaking. But, there are negative impactson student's learning, where the students are dependent and passive by waiting for teacher feedback.